1968
DOI: 10.1126/science.160.3831.1006
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A-Induced Synthesis of Alkaline Phosphatase

Abstract: Incorporation of radioactive leucine into electrophoretically separated proteins from mouse tail epidermis indicates that synthesis of alkaline phosphatase is stimulated by vitamin A. It is suggested that some of the diverse effects of vitamin A may be the result of alkaline phosphatase induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1969
1969
1993
1993

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It has been suggested that vitamin A regulates alkaline phosphatase activity in some cell types [5]. In the same study, similar results have been found in cultured prostatic cells of normal and malignant origin and found that retinoic acid causes the rapid RNA and protein synthesis-dependent induction of alkaline phosphatase.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It has been suggested that vitamin A regulates alkaline phosphatase activity in some cell types [5]. In the same study, similar results have been found in cultured prostatic cells of normal and malignant origin and found that retinoic acid causes the rapid RNA and protein synthesis-dependent induction of alkaline phosphatase.…”
Section: Discussionsupporting
confidence: 75%
“…The level of enzyme activity is an indicative of liver, bone and thyroid function [4]. Vitamin A has a specific effect on alkaline phosphatase activity, which is independent of keratinization [5]. Alkaline phosphatase activity is particularly abundant in intestine, kidney and bone [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three "broad spectrum" and specific alkaline phosphatase "inducers" were given to TB and HP: phenoharhital (24). vitamin A (19). and corticosteroid (10).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an associated stimulation of RNA synthesis (Zachman, 1967;Lukacs, Christophers & Braun-Falco, 1971). Induced formation of a new iso-enzyme of alkaline phosphatase by mouse epidermal cells is stimulated by retinyl acetate (Riley & Spearman, 1968), and similar distributions of this enzyme induction after applications of other forms of vitamin A suggest that all act in the same manner on mouse epidermis. Formation of alkaline phosphatase in the scale epidermis indicates that the vitamin penetrates directly through the keratin layer.…”
Section: Discussionmentioning
confidence: 95%